Perinatal outcomes in neonates referred to social services in a tertiary neonatal intensive care unit from a resource-limited setting: a five-year study - Dogan Kocabıyık, Nazan Neslihan; Salihoglu, Ozgul (Frontiers in Pediatrics, 2026)
BackgroundBeyond medical complexity, social determinants of health and social vulnerability have emerged as factors shaping perinatal and neonatal outcomes among socially vulnerable families in neonatal intensive care units. However, data integrating maternal, neonatal, and social risk factors among infants requiring social-service referral during neonatal intensive care unit (NICU) hospitalization remain limited, especially in resource-limited settings.Study designA retrospective cohort study was conducted including all neonates who received a formal social-service consultation between January 2020 and December 2024, and a comparison group of infants hospitalized without referral.MethodsData were extracted from electronic medical records and social-service notes. Maternal variables included age, marital status, antenatal visit frequency, prenatal testing, smoking or substance use, hematologic parameters, and antenatal corticosteroid administration. Neonatal variables included birth weight, gestational age, APGAR scores, NICU diagnoses, prematurity-related morbidities, respiratory support, thyroid function tests, hearing-screening results, and hospitalization duration. Social-service notifications were categorized as legal/judicial reasons, parental psychosocial or functional challenges, parental care risks, and socioeconomic vulnerabilities. Group comparisons used t-tests, Mann–Whitney U tests, and χ2/Fisher's exact tests. Logistic regression identified independent predictors of referral.ResultsA total of 193 neonates were assessed. Referred infants (n = 96) were born to younger mothers with significantly higher rates of adolescent pregnancy, unmarried status, inadequate antenatal care, lower maternal hemoglobin levels, and higher smoking/substance use. Referred infants had lower 5-min APGAR scores and higher rates of low birth weight, neurological diagnoses, bronchopulmonary dysplasia, abnormal thyroid function, prolonged hospitalization, and bilateral or unilateral hearing-screen failure. Mortality was significantly higher in the referred group. In multivariate analysis, lack of legal marriage (OR: 0.05), absence of antenatal care (OR: 0.12), lower maternal hemoglobin (OR: 0.41), lower neonatal TSH levels (OR: 0.75), and longer hospitalization (OR: 1.07) remained independent predictors of social-service referral. Non-Turkish nationality was significant in univariate analysis but not in the adjusted model.ConclusionInfants referred to social services in the NICU represent a distinctly vulnerable population characterized by inadequate maternal antenatal care, unmarried status, maternal anemia, and substance exposure. Integrating early social-risk screening into routine antenatal care and strengthening multidisciplinary perinatal–social collaboration may improve outcomes in high-risk families.